Control of Apple Fruit Rot Caused by Alternaria porri and Alternaria mali by Using Hot Water Treatment and Some Inorganic Salts - Imhammed, Aly Abdulla; Alhdad, Gazala M. (Scientific Journal for Faculty of Science-Sirte University, 2022)
Apple rot is one of the most important apple diseases worldwide. The disease causes significant losses in both the quantity and quality of apple fruits. In this study, the antifungal activity of hot water treatment and salts were investigated against apple fruit rots caused by Alternaria porri and Alternaria mali. Linear growth of tested fungi was inhibited at 5ºC, however, growth was increased by increasing storage temperature degree from 15ºC to 25ºC and decreased at 35ºC. On the other hand, hot water treatment at 55ºC significantly reduced the decay index and severity of infection. When salts such as potassium bicarbonate (KCO3), calcium chloride (CaCl2), sodium bicarbonate (NaHCO3) and ammonium bicarbonate (NH4CO3) was applied, a significant reduction in linear growth and fruit rot incidence was noticed using potassium bicarbonate. Calcium chloride, ammonium bicarbonate and sodium bicarbonate greatly inhibited growth of A. porri and A. mali. The most effective inhibitor of fruit decay was potassium bicarbonate and calcium chloride.